2021
DOI: 10.1007/s11804-021-00214-1
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Effect of the Side Hull Symmetry on the Resistance Performance of a Wave-Piercing Trimaran

Abstract: This paper presented the results of an experimental investigation into the resistance performance of a wave-piercing trimaran with three alternative side hull forms, including asymmetric inboard, asymmetric outboard, and symmetric at various stagger/ separation positions. Model tests were carried out at the National Iranian Marine Laboratory (NIMALA) towing tank using a scale model of a trimaran at the Froude numbers from 0.225 to 0.60. Results showed that by moving the side hulls to the forward of the main hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…For the preliminary design of the trimaran, the state of the art was taken into account. Recent investigations on the design of trimaran have researched the structure [35][36][37][38], the outrigger layout [39][40][41][42], optimization to reduce resistance [42][43][44][45], seakeeping and stability performances [46][47][48], and the design method itself [49][50][51]. From a structural point of view, Daidola et al [35] discussed preliminary structural design procedures for a large highspeed sealift trimaran, while Tang et al [36] applied structure monitoring technology, and Jia et al [37] proposed a lightweight design of a trimaran bulkhead using structural topology optimization.…”
Section: Not Implemented Properlymentioning
confidence: 99%
See 2 more Smart Citations
“…For the preliminary design of the trimaran, the state of the art was taken into account. Recent investigations on the design of trimaran have researched the structure [35][36][37][38], the outrigger layout [39][40][41][42], optimization to reduce resistance [42][43][44][45], seakeeping and stability performances [46][47][48], and the design method itself [49][50][51]. From a structural point of view, Daidola et al [35] discussed preliminary structural design procedures for a large highspeed sealift trimaran, while Tang et al [36] applied structure monitoring technology, and Jia et al [37] proposed a lightweight design of a trimaran bulkhead using structural topology optimization.…”
Section: Not Implemented Properlymentioning
confidence: 99%
“…The outrigger layout, which refers to the longitudinal and transverse distance between the main hull and the two outriggers, can be optimized to reduce the interference wave resistance between the main hull and the outriggers by means of both numerical [39] and experimental studies [41]. The results of Ghadimi et al [39] showed that trimaran vessels have suitable dynamics with lower longitudinal side bodies and large transversal distances, which was also confirmed by the work of Sun et al [52], in which the flow field between the main hull and demihull can be observed.…”
Section: Not Implemented Properlymentioning
confidence: 99%
See 1 more Smart Citation